Indian Black-Berry (Syzygium cumini) Seed Flour in Diabetic Study - Lakshmi, E. (Technological Innovation in Pharmaceutical Research Vol. 7, 2021)
Objective: To optimize recipes incorporating Indian black berry (Syzygium cumini) seed flour in biscuits for its organo-leptic feel and assess its impact on the anthropometric status of Type 2 diabetes mellitus. Methods: The study was designed to include 20 Type 2 and 20 normoglycaemic control. Biscuits were prepared using four blends (10 g, 15 g, 20 g and 25 g) of Syzygium cumini seed flour (SCSF) with a control. The diabetic subjects were supplemented with Indian blackberry (Syzygium cumini) seed flour (20 g) biscuits. Nutritional status were assessed like body mass index (BMI) and waist hip ratio (WHR). Results were analysed statistically by two -way anova and paired ‘t’ test. Results: Statistically there was significant difference (P<0.001) in flavor and taste perception between diabetics and Normoglycemic. The mean fasting and Post prandial glucose level decreased much (P<0.001). There was significant(P<0.001) decrease in the body mass index and waist hip ratio.